KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA FIXIE ZENITH DISURABAYA - FIKRI, MUHAMMAD (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
Needs for a clean air are encouraging public awareness to reduce the air pollution, one of which is by cycling. The phenomenon that occurs is that cycling is now start to life style are public, in line with Indonesian government efforts to promote cycling through "Car Free Day". More that produce variants of bicycles, including the most favored category Fixie cycle, namely the Fixie Zenith which famous by its comfort for driving in the big cities. This research aims to determine the effect of product quality and price simultaneously and partially to the purchase decision of Fixie Zenith Bike. Results showed that simultaneous Quality Product and Price affect the purchase decision. While the magnitude Results showed that the Quality Product are partially shown to have high significant influence on purchase decision. Keywords: Quality Product, Price, Purchase Decision.